Type tricks your personal guide to type design - Beier, Sofie (Amsterdam BIS Publishers, 2017)
Type Tricks' is about typographical rules and the underlying structure of the work process in the design of new typefaces. In that way, it is both a reference book and a user manual. In an illustrative format, it presents the different stages of type design in an easily accessible manner.
"200+ tips"--Cover
Keywords: Graphic design (Typography); Type and type-founding -- Design